The impact of the Indochina War on the way of life of Savannakhet province, Lao PDR, to creation of contemporary art: - Paigapat, Yuttana (Asian Journal of Traditional and Innovative Arts and Textiles, 2023)
‘The impactof the Indochina War on the way of life of Savannakhet Province,Lao PDR, to creation of contemporary art’ is the article based on the study of the situational duration from the year 1954 A.D. to present year as its main time frame purposively for the contemporary art creation. In order to understand comprehensively the way of life of the people in particular conditions, area and their stages and created artistic inspiration, methodologies designed to study the impact from the Indochina War to the way of life of Laotians as a specific location and in certain period of time. It is the mixed research by having the qualitative methodology and the arts creation researches together in the same process. The target groups were experts, practitioners, related figures, the war-impacted persons and vulnerable persons. The methodological tools were survey guidelines, semi-structural interview guidelines in order to collect data and information to be analyzed and created contemporary art. By applying conceptual art, creativity concept, composition art concept, Functionalism theory, Semiotic theory, Post-modern theories and Reconstructionism theories in the study process aimed at the art creation. The research findings included the Indochina War history and background is divided into 2 periods; Indochina under French protectorate during the year 1893 to 1954 A.D. ended at the defeated French by Indochina’s communist party and during under United States of America-USA’s influences and occupational war zone from the year 1954 A.D. ended in the year 1975 A.D. when USA was defeated by the communist movement in the subregion and led to Lao PDR establishing from the year 1975 A.D. to present. In forming the Lao PDR, there were two-war times by which had many impacts to Savannakhet Laotians’ way of life. There are 6 aspects of impact; mental, social, environmental, economic, cultural and educational. From the impacts, the researcher brought data and information in with its’ analysis to create main concept in the creation process as a conceptual art that presented in the 2 pieces of contemporary art of which reflect the researcher’s concept well.